SECONDARY PLASMA CELL LEUKAEMIA - Idris, Muhammad; Farid, Jamila; Javed, Nasreen (Journal of Ayub Medical College Abbottabad, 2020)
Plasma cell leukaemia is a clinical condition in which plasma cells circulating in the peripheral blood constitute > 20% of white blood cells (WBC) and there is evidence of plasma cell monoclonality. It is important to be diagnosed early for better treatment outcome. Although it is a rare disease, cases have been reported from Pakistan and other countries (including our neighbouring countries), hence making this case report. After taking history of present and past ailments, physical examination was carried out. Blood and bone marrow sampling were done after taking informed written consent from the patient. Blood samples were obtained in plain bottle, anticoagulated bottle and bone marrow was obtained from posterior iliac spine under 2% lignocaine. Plasma cell leukaemia is a rare and aggressive disease, difficult to diagnose and treat, requires early recognition and therapeutic intervention. Keywords: Plasma cell leukaemia; Multiple myeloma; Monoclonal gammopathy; Plasma cell myeloma; Solitary plasmacytoma